PERAN GURU SLB DALAM OPTIMALISASI POTENSI AKADEMIK ANAK TUNADAKSA - Susilowati, Diana; Estu Harsiwi, Nova (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Physical disability (tunadaksa) is a condition that affects an individual's physical abilities and interferes with their capacity to carry out daily activities. Children with physical disabilities face challenges not only physically, but also socially and psychologically, which can significantly influence their personality development and self-concept. The social environment plays a crucial role in building their self-confidence and adaptability, especially during adolescence—a period marked by change and identity formation. This study was conducted at SLB PGRI Kamal, a representative educational institution serving children with special needs. Using a conceptual approach based on literature review, this study explores the importance of environmental support and symbolic meaning in the social lives of children with physical disabilities. The findings indicate that social acceptance and healthy interactions positively impact their personality development. The self-concept and social identity of children with physical disabilities are shaped by social symbols that are mutually agreed upon within group interactions. Therefore, a humanistic, inclusive approach that emphasizes individual potential is essential to support their growth and integration into society. It is hoped that this study will serve as a foundation for developing inclusive educational and social strategies tailored to children with physical disabilities.